Pragmatic Identity in China and the US Real Estate Advertising: Critical Pragmatic Analysis - xu, elin (Advances in Social Sciences Research Journal, 2020)
This research attempts to find out similarities and differences of values through comparison of pragmatic identities constructed in china real estate advertising and that in the US real estate advertising. The study selected 50 Chinese and 50 American electrical real estate advertising.to analyze pragmatic identities constructed in these advertisements and concluded 16 kinds of identities. Both American and Chinese advertisers tend to presuppose consumers’ identity to advertise real estate although explicit linguistic resources regarding identity such as champion are also used to construct identity. Advertisers tend to appeal and provoke consumers’ purchase desire so that they construct different identities according to Maslow’s hierarchy of needs especially belonging (love) and self-realization needs. As regard to differences of identities embodied in Chinese and American real estate advertising, Hofstede’s cultural dimensions are adopted to explain.